Análisis del efecto antifúngico de los hidrolatos ajo-ají sobre la monilia (Moniliophthora Roreri) (2021)
Every day cocoa crops face problems due to diseases caused by fungi, insects and bacteria, which decrease the quality of the final product, generating large economic losses, which is why agricultural, chemical and genetic controls are commonly used to reduce their effects; However, there is a new trend to use biopreparations to minimize the negative impacts of these treatments on soil fertility, on physicochemical changes of the fruit and on water, air and land contamination.